The Relationship Between Female Nurses' Dual Role Conflict And Work Motivation At Syekh Yusuf Gowa Hospital - Rauf, Syamsiah; Amal, Andi Adriana; Nurkhalishah, Nurkhalishah; Hidayah, Nur (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2025)
Background: Nurses' work motivation is still a problem in nursing services in hospitals, which is the main key to the success of health service development. Nurses who feel dual role conflict is a severe problem that can affect work motivation, especially in women.Purpose: This study aims to find out the relationship between dual role conflict of female nurses with work motivation at Syekh Yusuf Gowa Hospital.Methods: This research design is quantitative with a cross sectional study approach. A total of 134 respondents were obtained by cluster random sampling. Data collection used questionnaires of dual role conflict and work motivation.Results: The results showed that the most female nurses' dual role conflict was in the low category of 74 respondents (55.2%) and the least was in the high category of 60 respondents (44.8%). Meanwhile, the most work motivation in the high category is 118 respondents (88.1%), and the least in the low category is 16 people (11.9%). Based on the cross-tabulation results of the Continuity Correction test, the p-value is 0.001.Conclusion: It is concluded that there is a significant relationship between the dual role conflict of female nurses and work motivation at Syekh Yusuf Gowa Hospital Therefore, it is important for nurses, especially female nurses at Syekh Yusuf Gowa Hospital, to manage psychological well-being so that the dual